2015
DOI: 10.1016/j.chemosphere.2014.10.006
|View full text |Cite
|
Sign up to set email alerts
|

Development and application of the adverse outcome pathway framework for understanding and predicting chronic toxicity: II. A focus on growth impairment in fish

Abstract: Adverse outcome pathways (AOPs) organize knowledge on the progression of toxicity through levels of biological organization. By determining the linkages between toxicity events at different levels, AOPs lay the foundation for mechanism-based alternative testing approaches to hazard assessment. Here, we focus on growth impairment in fish to illustrate the initial stages in the process of AOP development for chronic toxicity outcomes. Growth is an apical endpoint commonly assessed in chronic toxicity tests for w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
38
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(40 citation statements)
references
References 244 publications
(302 reference statements)
2
38
0
Order By: Relevance
“…This has led to the development of integrated testing strategies which use a combination of computational models (such as structural alerts, read across, QSARs and modelling) along with in vitro testing in order to develop alternative methods. The integration of alternative methods with pathways of toxicity has, in part, also catalysed the formation of the Adverse Outcome Pathway (AOP) framework concept (Ankley et al, 2010;Groh et al, 2015;Vinken, 2013Vinken, , 2015. An AOP describes the causal linkage between a molecular initiating event (MIE) and an adverse outcome at individual or population levels (Patlewicz et al, 2015).…”
Section: Aop Developmentmentioning
confidence: 99%
“…This has led to the development of integrated testing strategies which use a combination of computational models (such as structural alerts, read across, QSARs and modelling) along with in vitro testing in order to develop alternative methods. The integration of alternative methods with pathways of toxicity has, in part, also catalysed the formation of the Adverse Outcome Pathway (AOP) framework concept (Ankley et al, 2010;Groh et al, 2015;Vinken, 2013Vinken, , 2015. An AOP describes the causal linkage between a molecular initiating event (MIE) and an adverse outcome at individual or population levels (Patlewicz et al, 2015).…”
Section: Aop Developmentmentioning
confidence: 99%
“…AOPs are extremely useful in deducing the key events linking an apical end point, such as reduced reproductive output, with a perturbation, such as particle ingestion, because they describe generalized motifs of biological response, or key events that are not necessarily specific to any one chemical or substance. For example, applying the AOP concept to growth retardation in fish allowed Groh et al (18) to distinguish the mode of action of cadmium, which reduced growth through increased metabolic demand, from the mode of action of pyrethroid pesticides and selective serotonin reuptake inhibitors, which reduced food intake through changes in behavior and appetite (18). In relation to microplastics, the situation is further complicated by their potential to associate with chemical contaminants and the as-yet-unknown extent to which these absorbed contaminants are transferred from the ingested particle into the organism's tissues.…”
mentioning
confidence: 99%
“…The overall effects on swimming suggest a possibility for outcomes related to higher-level biological processes (SĂĄrria et al, 2011;Groh et al, 2015), and further research is therefore, warranted to explore and understand the implications of such responses in the context of ecotoxicology (Weis et al, 2001;Melvin and Wilson, 2013). For example, the observed differences in angular velocity may have implications for predator avoidance ability (BenhaĂŻm et al, 2012), and this could be particularly important in juvenile fish.…”
Section: Resultsmentioning
confidence: 87%
“…This raises concerns about the potential for wastewater discharge and emerging wastewater contaminants to impact aquatic organisms, and highlights the need for research exploring sub-lethal toxicological outcomes in wildlife (Boxall et al, 2012;Rudd et al, 2014). Alterations to an animal's growth, energy reserves, and/or functional performance (e.g., swimming abilities) are all indicative of potential broader ecological concerns that may result from exposures, since these endpoints often correlate well with higherlevel biological processes like survival and reproduction (SĂĄrria et al, 2011;Amiard-Triquet et al, 2012;Groh et al, 2015). Several studies have described increased growth and condition in fish exposed to domestic wastewater (Clark and Fraser 1983;Galloway et al, 2003), and altered energy status and swimming performance have been observed with exposure to various complex effluents (Adams et al, 1989;Smolders et al, 2003;Goertzen et al, 2011).…”
Section: Introductionmentioning
confidence: 97%